The Whale Bone Seat of Great Yarmouth - d’Isa, Raffaele (Natural History Sciences, 2025)
Monumental chairs and thrones have taken the most varied and artistic forms over the course of the ages. One of the most bizarre is the Whale Bone Seat of Great Yarmouth, a maritime town in the County of Norfolk in England. This monumental chair, which over the course of the ages has intrigued historians, naturalists, journalists, and artists, was made from the skull of a sperm whale and kept at first outside and subsequently inside St. Nicholas’ Church of Great Yarmouth. The oldest historical records mentioning it date back to 1606, when the Seat received a coat of paint. However, it appears that the Seat already existed before this decorative intervention and that it was created from the cranial bones of a whale washed on shore in the late 16th century. Traces of the Seat were lost after the Second World War, when the Nazi aviation dropped more than 1500 bombs over Great Yarmouth, destroying almost completely St. Nicholas’ Church. In the present article, after having provided a description of the Seat, I investigate its possible origin, and I trace the history of this haunting and mysterious object from the 16th to the 20th century.